Non-target effect of pesticides in rice environment - G, Basana Gowda; Ray, Aishwarya; Adak, Totan; Sahu, Madhusmita; Sahu, Nandini; Pandi, Guru Pirasanna; Patil, Naveenkumar B.; M, Annamalai; Rath, Prakash Chandra (ORYZA-An International Journal of Rice, 2021)
Agriculture has always been affected by intractable pests. Conventional agriculture still relies on the use of several pesticides to control various pests to ensure the yield of the crop and to feed a constantly growing population. To reduce the pest menace, the fatuous behavior of people as well as a natural proclivity towards the use of pesticides in a non-judicious manner, has caused several ecological backlashes such as secondary pest outbreak, pest resurgence and non-target organism's exploitation. Effects of pesticides on non-targetorganisms area worldwide concern and contention are the basis for most legislation regarding usage of specific pesticides. Pesticides, besides their effect on pests, would also affect several beneficial non-targets. The effect of pesticides could be lethal and may prove catastrophic or sublethal and stimulate the growth and development of non targeted biota's. Hence, this review approaches well-analyzed hindsight regarding the effect of pesticides on the natural enemies as well as other non-target organisms present in the rice agroecosystem.